Selenium nanoparticles as a nutritional supplement - Skalickova, Sylvie; Milosavljevic, Vedran; Cihalova, Kristyna; Horky, Pavel; Richtera, Lukas; Adam, Vojtěch (Nutrition, 2017)
Selenium is an essential trace element in the diet, required for maintenance of health and growth; however, its toxicity could cause serious damage depending on dose and chemical form. Selenium nanoparticles (SeNPs) represent what we believe to be a novel prospect for nutritional supplementation because of their lower toxicity and ability to gradually release selenium after ingestion. In this review, we discuss various forms and types of SeNPs, as well as the way they are synthesized. We also discuss absorption and bioavailability of nanoparticles within the organism. SeNPs demonstrate anticancer and antimicrobial properties that may contribute to human health, not only as dietary supplements, but also as therapeutic agents.
Keywords: Nanoparticles; Dietary Supplements; Trace Elements; lidé; antiinfekční látky; selen; Antineoplastic Agents; Anti-Infective Agents; protinádorové látky; stopové prvky; potravní doplňky; Selenium; nanočástice; Humans